Study on the Synchronous Instability Mechanism of the Coal Wall and Direct Roof of High Soft Coal Seam - Baojie Fu; Jiawen Li; Min Tu; Ningping Jin (Geofluids)
The advanced mining stress on a large working face can easily lead to the failure of the roof and coal mass; coal wall spalling and roof caving occur. The degree of coal wall failure and the depth of the plastic fracture zone are closely related to the advanced mining stress. The mechanical analysis model is established, and the stress distribution in the fracture and plastic zone is analyzed by the elastic-plastic theory, and the depth function expressions of two zones are determined. Comparative analysis of the factors affecting mining strength shows that the mining depth, mining height, and strength of coal are the key factors affecting the stability of the coal wall. The A1 coal of Zhangji mine in Huainan is soft and thick, and the direct roof is easily separated by the organic membrane, which is easy to form arc-shaped sliding instability. The increase in the unsupported roof area causes the direct roof caving and reduces its bearing capacity and stiffness. It is unable to provide enough support for the broken block of the overlying key stratum, which makes the broken block reverse rotation and further aggravate the roof fall; the synchronous instability of the coal wall and direct roof is formed.